A faunistic survey of digenean larvae infecting freshwater snails Biomphalaria, Radix and Bulinus species in the Lake Victoria and Mindu dam, Morogoro in Tanzania - Chibwana, Fred; Nkwengulila, Gamba (Tanzania Journal of Science, 2017)
Biomphalaria and Bulinus spp have been reported in Tanzania as vectors of Schistosoma mansoni and Schistosoma haematobium respectively. Thus most schistosomiasis control efforts have focussed on elimination of these molluscs in freshwater systems or deworming infected persons. In addition almost there is limited information of larval trematodes infecting freshwater snails in Tanzania and whether the trematode antagonism found elsewhere could be used for control of schistosomiasis. We report and describe larval digeneans infecting Biomphalaria pfeifferi, Bulinus spp and Radix natalensis, snails collected at Mindu dam, Morogoro and Mwanza gulf of the Lake Victoria from January 2011 to January 2012. Out of a total 9194 snails, belonging to Biomphalaria pfeifferi, Bulinus tropicus and Radix natalensis, collected from Mindu dam and the Mwanza gulf, Lake Victoria, 678 (7.34%) were infected with 14 larval trematode species: 3 xiphidiocercariae, 6 furcocercariae, l gymnocephalous cercariae, 1 amphistome, 2 echinostome and 1 undescribed metacercaria. From 386 infected B. pfeifferi 67 (1.69%) were infected with S. mansoni, the causative agent of intestinal schistosomiasis. These findings show that despite the increased effort to control schistosomiasis and other neglected tropical diseases in Tanzania, the diseases are still highly prevalent in freshwater systems. However, the absence of trematode antagonism or low multiple infections mean redia cannot coexist with sporocysts, hence can be used for control of schistosomiasis Keywords: Bulinus, Biomphalaria, Radix, Digenean larvae, neglected tropical diseases